Quantifying fruit quality affected by mechanical impact for selected apple varieties. Issue 17 (2018) - Fu, Han; Duan, Jieli; Karkee, Manoj; He, Long; Chen, Du; Sun, Daozong; Zhang, Qin
Abstract: To obtain baseline information for providing sufficient protection during localized shake-and-catch harvesting, the potential of fruit quality on top, middle and bottom surface zones of 'Jazz', 'Granny Smith' and 'Envy' apples was assessed when respectively impacted by aluminum and three different cushioned surface materials using a developed pendulum-type device. Three types of 12.7 mm thick Polyurethane foam pieces with 2.1 (Foam 1), 4.8 (Foam 2), and 9.7-11 (Foam 3) kPa deformation pressure were selected as the cushioning materials. Based on USDA Grades and Standards for fresh market apples, the categories of Extra Fancy Class 1 (no bruising), Extra Fancy and Fresh-market percentages were used to evaluate fruit quality with varying impact levels. According to equivalent principle of energy, equivalent drop heights of fruits were converted from impact forces created by surface materials impacting fruits. The fruit quality patterns with varying equivalent drop heights were determined for each of the three apple varieties. The results showed that Extra Fancy Class 1 grade was maintained within the equivalent drop heights of 24, 50 and 54 cm for 'Jazz' apples, 8, 18 and 38 cm for 'Granny Smith' apples, and 7, 26 and 34 cm 'Envy' apples when catching surface cushioned by Foam1, 2 and 3 respectively. To achieve better protection for higher drop heights, it would be reasonable to suggest the deformation pressure of the series of cushioning material used could be 4.8-11 kPa for 'Jazz' apples whereas the same for 'Granny Smith' and 'Envy' apples could be over 11 kPa.